The Methods of PH WINS 2017: Approaches to Refreshing Nationally Representative State-Level Estimates and Creating Nationally Representative Local-Level Estimates of Public Health Workforce Interests and Needs - Leider, Jonathon P. (J Public Health Manag Pract, 2019)
CONTEXT: The Public Health Workforce Interests and Needs Survey (PH WINS) was first fielded in 2014 and is the largest public health workforce survey in the nation. This article elucidates the methods used for the 2017 PH WINS fielding. PROGRAM OR POLICY: PH WINS was fielded to a nationally representative sample of State Health Agency Central Office (SHA-CO) staff, as well as local health department (LHD) staff. The instrument largely mirrored 2014, though the training needs section was revised, and a validated item measuring burnout in staff was added. IMPLEMENTATION: Staff lists were collected directly from all participating state and local agencies. Forty-seven state health agencies (SHAs), 26 large LHDs, and 71 midsize LHDs participated. All SHAs were surveyed using a census approach. The nationally representative SHA-CO frame is representative of all central office staff members. The nationally representative local frame was a complex survey design, wherein staff from LHDs were randomly sampled across 20 strata, based on agency size and geographic region. Staff were also contributed with certainty from large LHDs in nondecentralized states. The frame is representative of staff at LHDs serving more than 25 000 people and with 25 or more staff members. Other LHDs are excluded, and so PH WINS is not representative of smaller LHDs. Balanced repeated replication weights were used to adjust variance estimates for the complex design. EVALUATION: Overall, 47 604 people responded to PH WINS in 2017 across all frames. PH WINS 2017 achieved a response rate of 48%. The design effect for the SHA-CO frame was 1.46 and was 16.42 for the local frame. DISCUSSION: PH WINS now offers a nationally representative sample of both SHA-CO and LHD staff across 4 major domains: workplace environment, training needs, emerging concepts in public health, and demographics. Both practice and academia can use PH WINS to better understand the perceptions and needs of staff, address training gaps, and work to recruit and retain quality staff.